2019
DOI: 10.1016/j.bbrc.2018.12.173
|View full text |Cite
|
Sign up to set email alerts
|

Connexin43 regulates osteoprotegerin expression via ERK1/2 -dependent recruitment of Sp1

Abstract: In bone, connexin43 expression in cells of the osteoblast lineage plays an important role in restraining osteoclastogenesis and bone resorption. While there is a consensus around the notion that the anti-osteoclastogenic factor, osteoprotegerin, is a driver of this effect, how connexin43 regulates osteoprotegerin gene expression is unclear. Here, we showed that loss of connexin43 decreased osteoprotegerin gene expression and reduced ERK1/2 activation. Conversely, overexpression of connexin43 increased osteopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…3C). Interestingly, it was recently reported that Cx43 expression in osteoblasts could alter ERK activity (38); in this case, Cx43 knockdown diminished ERK phosphorylation, whereas overexpression increased ERK phosphorylation. This is certainly distinct from our data, as we saw an ERK effect in animals expressing the lowest total levels of Cx43 (old Cx43 CK1 mice, Fig.…”
Section: Discussionmentioning
confidence: 90%
“…3C). Interestingly, it was recently reported that Cx43 expression in osteoblasts could alter ERK activity (38); in this case, Cx43 knockdown diminished ERK phosphorylation, whereas overexpression increased ERK phosphorylation. This is certainly distinct from our data, as we saw an ERK effect in animals expressing the lowest total levels of Cx43 (old Cx43 CK1 mice, Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Numerous evidences reveal that ERK pathways play an important role in promoting cell motility [28,29]. Although, several studies indicate that ERK1/2 signaling pathway regulates Cx43 [37][38][39][40][41]; other reports involves Cx43 in the regulation of ERK1/2 signaling pathway [30][31][32][33]. Our data demonstrate that ERK1/2 phosphorylation was recovered by the addition of either StarD7 isoforms but not by exogenous Cx43, indicating that in this cell model ERK1/2 phosphorylation is upstream of Cx43.…”
Section: Plos Onementioning
confidence: 50%
“…Numerous evidences reveal that ERK pathways are required to promote cell motility [28,29]. In addition, several reports indicate that Cx43 is involved in regulating ERK1/2 signaling [30][31][32][33][34]. Thus, we explored the expression of p-ERK1/2 in StarD7-silenced cells.…”
Section: The Decrease In Htr-8/svneo Cell Migration Was Accompanied W...mentioning
confidence: 99%
“…Upregulation of Adipoq mRNA in WAT and in differentiating EMSCs supports the idea that increased production of adiponectin or other adipokines, or endocrine factors may in part explain increased glucose utilization and energy consumption by cKO Tw2 mice. We and others have shown that Cx43 modulates the expression of factors relevant to bone homeostasis via transcriptional regulation (42,43), and a similar mechanism might be at play in the adipogenic lineage. It is also possible that adipokines produced by BAT (batokines) may play a role, as Cx43 is abundantly expressed in BAT and is upregulated by high caloric intake.…”
Section: Discussionmentioning
confidence: 73%